Escherichia coli-derived recombinant human bone morphogenetic protein-2 combined with bone marrow-derived mesenchymal stromal cells improves bone regeneration in canine segmental ulnar defects. Issue 1 (December 2016) - Itoi, Takamasa; Harada, Yasuji; Irie, Hiroyuki; Sakamoto, Michiko; Tamura, Katsutoshi; Yogo, Takuya; Soeta, Satoshi; Amasaki, Hajime; Hara, Yasushi; Tagawa, Masahiro
Abstract Background Large bone defects in canines usually require assistance to achieve healing. Implantation of osteoinductive factors can promote bone healing, while transplantation of osteoprogenitor cells can enhance bone regeneration. We hypothesized that implantation of an osteoinductive factor, recombinant human bone morphogenetic protein-2 (rhBMP-2), combined with osteoprogenitor cells, bone marrow-derived mesenchymal stromal cells (BMSCs), would synergistically promote bone healing. In this study, we examined the combined effects ofEscherichia coli -derived rhBMP-2 and BMSCs on bone healing after implantation into canine ulnar defects. Results Critical-sized osteoperiosteal segmental defects (2.5 cm) were created in the ulnae of healthy female beagle dogs, and implanted with combinations ofE. coli -derived rhBMP-2 (560 or 140 μg) and autologous BMSCs (107, 105, or 0 cells). In the present study, 18 forelimbs of nine healthy purpose-bred female beagles were used. All six treatment groups contained three forelimbs, and the animals were euthanized after 12 weeks. The control groups (560 and 140 μg/0 cells) were cited from our previous study to reduce the number of experimental animals. Radiographically, the regenerated bone width was significantly increased in the 560 or 140 μg with 107 and 105 cells groups compared with the 0 cells groups. By quantitative CT, the bone mineral density was higher in the 560 μg with 107 and 105 cells groups, while non-uniformity of the bone mineral density was improved in the 560 μg with 107 and 105 cells groups and 140 μg/107 cells group. Mechanically, the maximum loads at failure were significantly higher in the 560 μg with 107 and 105 cells groups. Histologically, the regenerated bone was well-developed and contained osteocyte-like cells marrow cavities, and vessels. However, the osteoclasts and osteoblasts were hardly observed. The osteocyte-like cell numbers were significantly higher in the 560 μg with 107 and 105 cells and 140 μg with 107 and 105 cells groups. Conclusions Implantation ofE. coli -derived rhBMP-2 and BMSCs led to significantly enhanced bone formation, with improved bone mineral density and reduced non-uniformity of the regenerated bone. Combined implantation of rhBMP-2 and BMSCs may be useful for promotion of bone healing in critical-sized defects in canines.